Optimization of resonant capacitance values for high-efficiency uninterruptible wireless power transfer system using CST software - Rawi, Muhammad Shawwal Mohamad; Baharom, Rahimi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This paper introduces an innovative methodology for optimizing resonant capacitance values (Cp and Cs) to enhance the efficiency of uninterruptible wireless power transfer (UWPT) systems, utilizing advanced computer simulation technology (CST) software. Precise tuning of resonant capacitance is critical for achieving optimal frequency matching, which directly influences system performance. The study focuses on three coil configuration strategies: standard coil configuration, coil integrated with ferrite, and coil enclosed within a casing and ferrite. These configurations were analyzed to identify the optimal capacitance values, resulting in significant efficiency improvements. Through comprehensive CST simulations, the capacitance values of Cp1, Cp2, and Cs were optimized to 140.8 nF, 105.6 nF, and 145.5 nF, respectively, achieving a remarkable power transfer efficiency of 99.61% in the casing and ferrite configuration. The proposed optimization methodology consistently achieved efficiencies exceeding 90% between the transmitter and receiver coils. Beyond simulation results, this research highlights the potential for real-world applications and underscores the importance of precise parameter optimization in advancing high-efficiency wireless power transfer systems. Future studies will aim to validate the findings experimentally and explore broader applications of the proposed system.